(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to the role and importance of terminological competence in the training of future philologists, which provides detailed information on the use of terms such as competence, its content, competence, professional competence, the role of professional competence in the pedagogical process, terminological competence. The factors, the main components of the formation of professional competencies in the future philologist teacher, the solution of professional problems that may arise in the course of professional activity, terminological competence, terminological competence are necessary for the training of philologists. The future specialist - the teacher must have a culture of speech, accuracy, precision, expressiveness of speech, purity of speech, its absence of various dialects, and in order to become a mature specialist must master the terms of the field, terminological competence. to be able to use it wisely in their professional activity, to express their opinion independently in this language orally and in writing, to be able to understand the terms of the specialty. Terminological competence and the role and importance of textbooks in its formation, the views of leading scholars and researchers on this process are described.